METHODS OF USING NATURAL GLAZE OF GURUMSARAY POTTERY SCHOOL (Academia Science Repository, 2023)
In this article, the establishment of the Gurumsarai pottery school in the Fergana Valley, which has a special place in Uzbek applied art, its main elements and the unique styles of this scientific school are analyzed.